Manajemen Penjadwalan Waktu Blokir Akses Internet pada Mikrotik RouterOS - Wahyu Hidayat M; Atika Dwiyanti Yusuf (PT. Lontara Digitech Indonesia, 2023)
Restricting internet access at certain hours allows for more efficient allocation of network resources and bandwidth. This limitation ensures that internet usage is not excessive, preventing the network from slowing down or being burdened by unproductive activities during critical hours. The research methodology employed involves the analysis of hardware and software requirements, network topology design, and network configuration. The research findings demonstrate the effectiveness of limiting internet access at specific times, supporting remote learning, and enhancing internet usage efficiency. System testing was conducted on Windows 10 and Debian 10, demonstrating the successful implementation of the scheduled blocking system. Although successful in simulation, this study has the potential to provide further benefits in real-world network environments.